FORMATION OF READINESS FOR DIALOGUE IN PROFESSIONAL ACTIVITY OF FUTURE MANAGERS OF FOREIGN ECONOMIC ACTIVIT - Elbrekht, Olha (Педагогічна освіта: теорія і практика, 2018)
The processes of globalization, the strengthening of intercultural communication in the world community define new requirements for the training of future managers of foreign economic activity – officials whose duty is to manage the organization, its subdivision, conducting a certain direction of work in the conditions of increasing cooperation and competition in the economy and business. Practice shows that today in this sphere, there are stronger connections and communication between representatives of different cultures, both in direct communication and in electronic communication. Today the goals of the education of managers are aimed not only at the formation of knowledge and skills in the organization of the management process, but also on the development of communication skills, the ability to clearly state their own opinion, to substantiate conclusions about solving problems, to convey knowledge and ideas. In the light of such demands, the problem of forming readiness for professional activities on a dialogical basis among students-future managers of foreign economic activity becomes more important. The purpose of the article is to carry out an analysis of the theoretical and practical foundations of future managers’ readiness for dialogue in the future professional activity and to determine the conditions for the successful implementation of this task by higher management education. The article substantiates the place and role of dialogical communication in the professional activity of managers of foreign economic activity, the importance of forming readiness for dialogue in the student age; the analysis of the concepts of “dialogue”, “interaction”, “dialogic interaction” are considered; the conditions and advantages of dialogical communication are examined, the levels of dialogical interaction in the educational process are determined; The modern forms and methods of training managers as an important factor in achieving the necessary level of preparedness of future international managers for dialogue are revealed; considerable attention is paid to the requirements for the study of a foreign language – an effective means of increasing the communicative abilities of students and their level of readiness for dialogic interaction.